Using mobile phones and social media to facilitate education and support for rural-based midwives in South Africa - Jennifer Chipps; Christoph Pimmer; Petra Brysiewicz; Fiona Walters; Sebastian Linxen; Thandi Ndebele; Urs Gröhbiel (AOSIS, 2015)
Background: Empirical studies show the value of mobile phones as effective educational tools to support learning in the nursing profession, predominantly in high income countries. Problem statement: The rapidly increasing prevalence of mobile phone technology in Africa nourishes hopes that these tools could be equally effective in lowly resourced contexts, specifically in efforts to achieve the health-related Millennium Development goals. The purpose of this study was to investigate the perception and use of mobile phones as educational and professional tools by nurses in lowly resourced settings. Methodology: A quantitative survey using self-administered questionnaires was conducted of rural advanced midwives. Results: Fifty-six nurses (49.6%) from the 113 rural-based midwives attending an advanced midwifery training programme at the University of KwaZulu-Natal, South Africa, filled in a questionnaire. The results showed that, whilst nurses regarded their technology competences as low and although they received very little official support from their educational and professional institutions, the majority frequently used mobile functions and applications to support their work and learning processes. They perceived mobile devices with their voice, text, and email functions as important tools for the educational and professional activities of searching for information and engaging with facilitators and peers from work and study contexts. To a lesser extent, the use of social networks, such as WhatsApp and Facebook, were also reported. Conclusion and recommendation: It is concluded that educational institutions should support the appropriate use of mobile phones more systematically; particularly in relation to the development of mobile network literacy skills.